Effects of Static Subnormothermic Preservation on Extended Warm Ischemic Porcine Kidneys Assessed by Normothermic Machine Perfusion and Renal Transplantation. (July 2018) - Sekijima, Mitsuhiro; Ariyoshi, Yuichi; Sahara, Hisashi; Kawai, Akihiro; Iwanaga, Takehiro; Murokawa, Takahiro; Ichinari, Yurika; Shimizu, Akira; Kusaka, Mamoru; Yamada, Kazuhiko
Abstract : Background: Donor organ shortage remains a critical issue. The donation after circulatory death (DCD) has the potential to increase the transplantable organs, however, DCD kidneys have a higher risk of acute kidney injury or delayed graft function due to the inevitable warm ischemia (WI). Although static cold storage (SCS) has been the gold standard for organ preservation to reduce metabolism and oxygen demand, various preservation methods have been examined including static subnormothermic storage (SSS) to maintain the physiologic and metabolic function of DCD organs especially in murine models. In this study, we evaluated the efficacy of SSS of extended WI porcine kidneys especially focused on 1) preoperative assessment by normothermic machine perfusion (NMP), and 2) longitudinal assessment by kidney transplant (KTx) using MHC-defined CLAWN miniature swine. Methods: Twelve porcine kidneys were subjected to 120-min WI followed by either 60-min SCS (4°C group) or SSS (22°C group) with extracellular-type solution. As experiment 1, the preserved 120-min WI kidneys were perfused with normothermic oxygenated red blood cells in Ringer's solution for 120 min using cardiopulmonary bypass. As physiologic parameters, renal blood flow (RBF) and urine output were monitored and intrarenal resistance (IRR) was calculated. As a metabolic parameter, blood gas analysis was performed to calculate oxygen consumption. As experiment 2, the preserved 120-min WI kidneys were transplanted into MHC-matched recipients with 12-days of continuous low-dose FK506. Renal function was monitored by serum creatinine (sCr) and renal biopsies. Results: All of the 120-min WI kidneys preserved for 60 min at either 4 or 22°C were successfully perfused using our established method of NMP for 120 minutes (Experiment 1). Although all kidneys showed the same macroscopic appearance during NMP, physiologic or metabolic parameters in 22°C group revealed better condition of the kidneys compared to 4°C group (22 vs 4°C: mean RBF 26.7 ± 4.7 vs 10.0 ± 0.0 ml/min, mean IRR 3.5 ± 0.5 vs 8.7 ± 0.1 mmHg/ml/min, total urine output 14.3 ± 5.3 vs 5.4 ± 3.6 ml, oxygen consumption 224 ± 39 vs 93 ± 16 ml/min/g), suggesting that 22°C-preserved WI kidneys show better outcome following KTx. In KTx model (Experiment 2), peak sCr of the animals in 22°C group was lower than that of 4°C group (22 vs 4°C: peak sCr 3.9 ± 0.6 vs 8.9 ± 0.3 mg/dl, p =0.0015). Kidney biopsies taken at 4 days revealed renal tubular necrosis over wide spread areas in 4°C group, while renal tubular necrosis was limited in 22°C group. Moreover, PCNA staining showed prompt regeneration of tubular epithelium in 22°C group. Conclusion: We demonstrated that SSS (22°C) of kidney grafts exposed to 120-min WI was more effective than SCS (4°C) assessed by NMP as well as KTx in miniature swine. To our knowledge, this is the first demonstration of the applicability of SSS in preclinical large animals.